2019
DOI: 10.1055/a-0994-0489
|View full text |Cite
|
Sign up to set email alerts
|

The Risk For Malignancy of the Thyroid Nodule is Modulated by Gender, Echotexture, and Intranodular Lymphocytic Thyroiditis

Abstract: Based on the American (Bethesda, 2017) or Italian (SIAPEC 2014) cytological categories of thyroid nodules, the risk of malignancy and management vary. This risk is 5–10% or<3% (benign or TIR2), 6–18% or<10% (AUS/FLUS or TIR3A), 10–40% or 15–30% (FN/SFN or TIR3B), 45–60% or 60–80% (suspicious or TIR4), 94–96% or 95% (malignant or TIR5). In 408 thyroid nodules evaluated cytologically, we computed the malignancy rate in each category considering gender (325 females, 83 males), echotexture (268 isoechoic, 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Another study evaluated how the rate of malignancy varied in each cytological category (from TIR2 to TIR5), taking into account gender, the echogenicity of the nodule and the presence or absence of intranodular chronic lymphatic thyroiditis (ICLT). In the TIR3b category, a rate over twice the expected 30% malignancy threshold was found in hypoechoic, ICLT-positive female nodules (80%), which contrasted sharply with the 38.5% rate of malignant tumours with the same characteristics but negative ICLT [37].…”
Section: Discussionmentioning
confidence: 80%
“…Another study evaluated how the rate of malignancy varied in each cytological category (from TIR2 to TIR5), taking into account gender, the echogenicity of the nodule and the presence or absence of intranodular chronic lymphatic thyroiditis (ICLT). In the TIR3b category, a rate over twice the expected 30% malignancy threshold was found in hypoechoic, ICLT-positive female nodules (80%), which contrasted sharply with the 38.5% rate of malignant tumours with the same characteristics but negative ICLT [37].…”
Section: Discussionmentioning
confidence: 80%
“…Fourth, the prevalence of ITN, TIR3A, and TIR3B among all FNACs was analyzed. Among those 20 studies reporting the overall number of biopsies performed during the study period, after excluding papers reporting only FNACs with ITN results, there were 16 studies eligible for this analysis [ 21 , 25 , 27 – 29 , 32 35 , 37 , 40 , 42 44 , 47 ]. Overall, the prevalence of ITNs among FNACs was 29.6% (95% CI 25–34.1), with high heterogeneity ( I 2 98%).…”
Section: Resultsmentioning
confidence: 99%
“…The latter observation has been reported previously in different studies that found that males with thyroid nodules displayed a higher incidence of malignancy than females. 13 , 14 …”
Section: Discussionmentioning
confidence: 99%
“…The latter observation has been reported previously in different studies that found that males with thyroid nodules displayed a higher incidence of malignancy than females. 13,14 The vast majority of thyroid nodules are known to be benign, while only up to 15% are malignant. 7 Results from the current study showed that most of the thyroid lesions in Najran were benign )72.5%(.…”
mentioning
confidence: 99%